STUDI LITERATUR : ANALISIS PENGGUNAAN E-COMIC SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN DI SEKOLAH DASAR - Novianti Baihaqi, Fitri; Maksum, Arifin; Aruwiyantoko, Anggit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the effectiveness of utilizing e-comic media in the context of Indonesian language learning, particularly in enhancing reading comprehension skills among elementary school students. This literature review compiles a range of significant research findings from 2020 to 2025, focusing on the effectiveness of e-comics as pedagogical tools in Indonesian language instruction, specifically in developing students’ reading comprehension abilities at the elementary level. The findings reveal that e-comic media has proven to be effective in improving students’ reading comprehension, as evidenced by a significant increase in post-test scores following the implementation of e-comics. The integration of visual elements and narrative within e-comics creates a more immersive and dynamic learning experience, enabling students to interpret and absorb reading material more effectively. The study also indicates that factors such as student motivation, media variation, and the integration of technology in the learning process greatly influence the success of this media's implementation. Based on these findings, it is recommended that teachers consider incorporating e-comics into Indonesian language instruction and encourage further research into the development of other digital media that can support reading comprehension in elementary education.